A Study of the Methodology of Maulana Abu Tahir Ishaq Khan Al-Madani in Tafsir "Umdat-ul-Bayan" - Muhammad Imaran; Dr. Abdul Hameed Khan Abbasi (jihat-ul-islam, 2020)
Being a scholar and preacher of Islam, Maulana Muhammad Ishaq Khan almadani’s dominant method in his exegesis is preaching method. Keeping the differences of sects of subcontinent in view, his main focus in the explanation of verses of the Holy Qur‘an is on to reforms people’s beliefs based on the different exegeses of the Holy Quran .According to him it is necessary that a Tafsirto be written in language that is suitable to the modern time and that provide satisfactory answers to the errors created by the innovators in the Islamic beliefs. The article is an endeavor to explore his method in his Tafsir: “ ‘Umdatul Bayan fi Tafsir alQur‘an” with the analysis of examples derived from his above mentioned Tafsir.